Exploring the role of Tibetan medicinal formula Qishiwei Zhenzhu Pills (Ranasampel) against diabetes mellitus-linked cognitive impairment of db/db mice through serum pharmacochemistry and microarray data analysis - Yan, Zhiyi; Zong, Yonghua; Zhang, Chengfei; Han, Zekun; Wu, Lili; Qin, Lingling; Liu, Tonghua (Frontiers in Aging Neuroscience, 2022)
Background Diabetes cognitive impairment (DCI) is a common diabetic central nervous system disorder that severely affects the quality of life of patients. Qishiwei Zhenzhu Pills (Ranasampel) is a valuable Tibetan medicine formula with the ability to improve cerebral blood vessels, protect nerves and improve learning and memory, which has also been widely verified in clinical and basic research. Currently, the prevention and treatment of DCI are still in the exploratory research stage, and the use of Ranasampel will provide new ideas and insights for its treatment. Objective This study is to explore the absorbed components in serum derived from Ranasampel using serum pharmacochemistry, then identify the potential mechanism of Ranasampel for the treatment of DCI through bioinformatics and microarray data validation. Methods The UPLC-Q-Exactive MS/MS-based serum pharmacochemistry method was conducted to identify the main active components in serum containing Ranasampel. Then, these components were used to predict the possible biological targets of Ranasampel and explore the potential targets in treating DCI by overlapping with differentially expressed genes (DEGs) screened from Gene Expression Omnibus datasets. Afterward, the protein–protein interaction network, enrichment analyses, hub gene identification, and co-expression analysis were used to study the potential mechanism of Ranasampel. Particularly, the hub genes and co-expression transcription factors were further validated using hippocampal expression profiles of db/db mice treated with Ranasampel, while the Morris water-maze test and H&E staining were used to assess the spatial learning and memory behaviors and histopathological changes. Results Totally, 40 compounds derived from Ranasampel had been identified by serum sample analysis, and 477 genes related to these identified compounds in Ranasampel, 110 overlapping genes were collected by the intersection of Ranasampel target genes and DEGs. Further comprehensive analysis and verification emphasized that the mechanism of Ranasampel treatment of DCI may be related to the improvement of learning and memory function as well as insulin resistance, hyperglycemia-induced neuronal damage, and neuroinflammation. Conclusion This study provided useful strategies to explore the potential material basis for compound prescriptions such as Ranasampel. These hub genes and common pathways also provided new ideas for further study of therapeutic targets of DCI and the pharmacological mechanism of Ranasampel.